First record of Hexacladia hilaris Burks (Hymenoptera: Encyrtidae) in Brazil and association with Chinavia erythrocnemis (Berg) (Heteroptera: Pentatomidae) - Marsaro Júnior, Alberto Luiz; Costa, Valmir Antonio; Panizzi, Antônio Ricardo (EntomoBrasilis, 2020)
Hexacladia hilaris Burks (Hymenoptera: Encyrtidae) is a parasitoid associated to several stink bug species in Costa Rica, Porto Rico and United States. In April 2018, at the Passo Fundo (28º15’46” S / 52º24’24” O), Rio Grande do Sul state, Brazil, specimens of H. hilaris were collected from Chinavia erythrocnemis (Berg) (Heteroptera: Pentatomidae). This is the first record of this parasitoid in South America as well as its association with C. erythrocnemis.